Optimización en adsorción - desorción de oro con resinas de intercambio iónico a partir de soluciones con iones tetracloroaurato - Guerrero León, Manuel (2015)
The study is part of the research that seeks alternatives to cyanide leaching of ores and / or concentrates gold from Casma, Ancash Region - Peru, why it is important to investigate the post-leaching processes. This research study presented as scale to pilot plant level and / or industrial through modeling of the adsorption process gold from research in laboratory tests on the adsorption of gold (III) ions on quaternary chitosan, under the influence of the variables: initial pH, adsorbent mass, ionic strength, initial metal concentration, and kinetics of adsorption, batch experiments by 20 ° C. The optimum values of these variables that influence the process modeling adsorption / desorption; select allowed the Langmuir adsorption isotherm, to show the greatest adsorption capacity. It was found in the proposed model using the optimized parameters, adsorption efficiency of 98.45%, after 3 hours of contact.